Internal Control System for Cash Disbursements at Makassar Subdivision - Abdul Wahab; Aris Baharuddin (Universitas Negeri Makassar, 2020)
This study aims to determine the Internal Control System for Cash Expenditures at Perum Bulog Subdivre Makassar. The type of research used is descriptive qualitative, namely the writer describes the results of observations and analyzes the data obtained in the field. The writing of this final project is the result of research conducted from June to July 2020.After analyzing and discussing the problem, the authors conclude that the Internal Control System for Cash Expenditures at Perum Bulog Subdivre Makassar has generally been implemented well. The organizational structure, system of authority and recording procedures, segregation of duties have been carried out properly, and employees whose quality is in accordance with their responsibilities are correct.